(3GbJWGa TbGFb GdfYeGf ef QjGV GdhGaj HhajGJ GdCYjGfs - (3EHQGgje Hf CMeO Hf eMeO Hf Ydj GdeYQha HGHf GdedG GdYHGSj GdbGOQj GdTGaYjs; (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3MeOoG def ENJGQ GdehJ dYHGOg Ke HOCg HJQGLe GdeMeOjf hGhdgG JQLeISjOfG eMeO Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3JQLeI MeO Hf SYjO Hf CMeO Hf fajS GdebQj s
(3GdehLhO efg GdCLRGA GdNeSI GdChdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B42 ; (3agQSJ GdecJHI GdCRgQjI (B- (3GdLRA (B5 - (3U (B333 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs